If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(z + 5)(-1z + -4) = 0 Reorder the terms: -3(5 + z)(-1z + -4) = 0 Reorder the terms: -3(5 + z)(-4 + -1z) = 0 Multiply (5 + z) * (-4 + -1z) -3(5(-4 + -1z) + z(-4 + -1z)) = 0 -3((-4 * 5 + -1z * 5) + z(-4 + -1z)) = 0 -3((-20 + -5z) + z(-4 + -1z)) = 0 -3(-20 + -5z + (-4 * z + -1z * z)) = 0 -3(-20 + -5z + (-4z + -1z2)) = 0 Combine like terms: -5z + -4z = -9z -3(-20 + -9z + -1z2) = 0 (-20 * -3 + -9z * -3 + -1z2 * -3) = 0 (60 + 27z + 3z2) = 0 Solving 60 + 27z + 3z2 = 0 Solving for variable 'z'. Factor out the Greatest Common Factor (GCF), '3'. 3(20 + 9z + z2) = 0 Factor a trinomial. 3((5 + z)(4 + z)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(5 + z)' equal to zero and attempt to solve: Simplifying 5 + z = 0 Solving 5 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + z = 0 + -5 z = 0 + -5 Combine like terms: 0 + -5 = -5 z = -5 Simplifying z = -5Subproblem 2
Set the factor '(4 + z)' equal to zero and attempt to solve: Simplifying 4 + z = 0 Solving 4 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + z = 0 + -4 z = 0 + -4 Combine like terms: 0 + -4 = -4 z = -4 Simplifying z = -4Solution
z = {-5, -4}
| 3.2x+9.5=1.8x-1.7 | | -2(5-4s+6t)-5s+t= | | (w-7)(w-5)=0 | | -3(4a-3)-2a=-18-5a | | 3(2-2n)=-6-3n | | -6b-21=-3(3b-5)-6b | | 5b-2=1 | | 5x+4x=6-7 | | 16f^2-24f=0 | | 6(y+5)-3(4y+2)= | | x^2-6x=440 | | .75x=.8 | | 2.4x-8.5=1.1x+0.6 | | .5x^2=60 | | 4y-8-2y=4 | | 16=2+31t-16t^2 | | 6*n+n=21 | | 12m-7n=3n+2 | | x+(2x-4)=11 | | 6x^2+3x=18 | | 13x+3=8x+18 | | 8x-(4x-7)=31 | | 2f(5)=3-4x^2 | | 18+y=2y-4 | | 4x^3-6x^2-8x+4=0 | | 4x^3-2x^2-8x+4=0 | | 10y^3(6-9y^5)=y | | r+s=120 | | r+2=120 | | (2x-5)+x=4 | | 3Y^2-5=2Y | | 1+3x-x=-4+2x |